If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = -4 + 8x Solving 28 = -4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 28 + -8x = -4 + 8x + -8x Combine like terms: 8x + -8x = 0 28 + -8x = -4 + 0 28 + -8x = -4 Add '-28' to each side of the equation. 28 + -28 + -8x = -4 + -28 Combine like terms: 28 + -28 = 0 0 + -8x = -4 + -28 -8x = -4 + -28 Combine like terms: -4 + -28 = -32 -8x = -32 Divide each side by '-8'. x = 4 Simplifying x = 4
| 6x-6y/-5z | | 6=5b+1 | | (2q+4)(3q+1)= | | 16x^4+26x^2+3=0 | | 690/a | | 1=d/4 | | X+.75x=65 | | 5cos^2x-cosx+3=0 | | -36-12x=48 | | 3-(5x+7)=17-8x | | 3(x+45)=2(x+40)+(2x) | | -6-9x+1=7x | | -2y+4x=-4 | | 4x-3(4x+21)=-143 | | -6-9+1=7x | | 4(d+50)=114 | | x^7+x^5+5=0 | | 10a-2ab= | | 8/x=-9 | | 7x+9y=192 | | 50x-80=70x+30 | | 4y+6(-2)y=10 | | 2(-4x+12)=144 | | 1.5(4-w)=-(1.5-8) | | 2logx-log(x+9)-log(x-9)=0 | | 4x=(2x+10) | | y-9=-5/7x | | 5x/2-3=-1 | | X-1/8=-10 | | 5x-2x+7-x=3x+4 | | x/2-9=19 | | 2logx+log(x+9)-log(x-9)=1 |